The Prevalence and Associations of Peripheral Retinopathy: Baseline Study of Guangzhou Office Computer Workers - Zhang, Shaochong; Peng, Manjuan; Liu, Rongjiao; Zhou, Xuezhi; Huang, Wenbin; Wei, Yantao; Zuo, Yajing; Zhang, Ting; Zhong, Lili (Journal of ophthalmology, 2018)
Purpose. To determine the prevalence of peripheral retinopathy and its associated risk factors among a sample of Guangzhou office computer workers. Methods. A cross-sectional study of Guangzhou Chinese computer workstations and operators in different departments and units of the Guangzhou Power Supply Bureau, China, in 2016. Peripheral retinopathy was recorded and analyzed using a scanning laser ophthalmoscope (SLO; Optos, Daytona, United Kingdom) and slit-lamp microscopy combined with a three-mirror contact lens. Results. The 1934 eyes of 967 subjects (513 females and 454 males) were included in this study. In total, 79.1% of the eyes were myopic in workers aged 20–29 years, 72.9% in workers aged 30–39 years, 62.2% in workers aged 40–49 years, and 43.4% in workers aged 50–59 years (p<0.001). Most eyes had optic nerve crescents (81.3%). Various peripheral degenerations were found: 7 eyes (0.4%) had microcystoid degeneration, 40 (2.1%) had peripheral pigmentary degeneration, 87 (4.5%) had lattice degeneration, and 4 (0.2%) had snail-track degeneration. Nineteen (1.0%) eyes had paving-stone degeneration, 11 (0.6%) eyes had a retinal hole or tear, and 16 (0.8%) eyes had chorioretinal degeneration. Multivariate regression confirmed that greater axial length (OR: 1.18 (1.03, 1.35), p=0.012) and more serious spherical equivalent (OR: 0.82 (0.77, 0.88), p<0.001) were significant risk factors for peripheral retinal changes. Conclusion. Peripheral retinal degenerative changes were found in a larger proportion of younger computer workers than older ones. Myopia is occurring in younger and younger people, accompanied by peripheral retinal degeneration.